Kajian Dampak Lingkungan pada Proses Produksi Pupuk NPK di PT. X Menggunakan Metode Life Cycle Assessment (LCA) - Aprilia Ningrum (Prosiding ESEC, 2023)
The fertilizer industry is one of the strategic sectors that can spur the national economy. This is because the fertilizer industry plays an important role in encouraging increased production in the agricultural sector which supports the national food security program in the future. NPK is a compound fertilizer consisting of several elements needed by plants including nitrogen, phosphorus and potassium. Broadly speaking, the process of making granulated NPK fertilizer consists of solid raw material feeding, slurry preparation, granulation process, drying and screening process, cooling and screening (cooling and screening), and coating (coating). Those who operate industrial activities will also have an impact on environmental changes such as the quality of water, soil and air. The Life Cycle Assessment (LCA) approach is an appropriate tool for analyzing to reduce pollution and environmental impacts during the product life cycle. In this study, the Open LCA 1.11.0 software was used. The purpose of this research is to determine the extent of the environmental impact of the LCA process by using a gate to gate approach in the production process. After knowing the magnitude of the resulting environmental impact, alternative improvements will be determined in order to reduce the amount of the resulting environmental impact.